2009
DOI: 10.1007/s11252-009-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Ant dominance in urban areas

Abstract: A survey was conducted to determine the distribution of dominant ants and factors that may influence their dominance in New Zealand cities. A new method of active ant trapping combining aspects of pitfall trapping and attraction to food baits was used to capture a sample of all ant species that attended baits. Fifty eight percent of the ant species present in New Zealand were recovered from 2202 traps, with multiple species catches in 245 traps. There was a strong latitudinal relationship in the distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
1
20
0
4
Order By: Relevance
“…performed at a single point in time along a gradient of urbanization (e.g., urban vs. rural areas, urban periphery vs. inner city, and urban green spaces vs. residential areas), or surveys have been conducted in several sites that have similar environmental condition (Yamaguchi 2004, Stringer et al 2009). While these approaches have allowed us to simplify the complicated effects of urbanization (Antonova 2005) and increased our understanding of the impact of invasive species on native communities (Touyama et al 2003, Stringer et al 2009), these approaches also have shown several associated problems.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…performed at a single point in time along a gradient of urbanization (e.g., urban vs. rural areas, urban periphery vs. inner city, and urban green spaces vs. residential areas), or surveys have been conducted in several sites that have similar environmental condition (Yamaguchi 2004, Stringer et al 2009). While these approaches have allowed us to simplify the complicated effects of urbanization (Antonova 2005) and increased our understanding of the impact of invasive species on native communities (Touyama et al 2003, Stringer et al 2009), these approaches also have shown several associated problems.…”
Section: Study Areamentioning
confidence: 99%
“…While these approaches have allowed us to simplify the complicated effects of urbanization (Antonova 2005) and increased our understanding of the impact of invasive species on native communities (Touyama et al 2003, Stringer et al 2009), these approaches also have shown several associated problems. To date, numerous studies have been undertaken at different sites for better understanding of the effect of urbanization on ant diversity in urban.…”
Section: Study Areamentioning
confidence: 99%
“…In New Zealand cities the Argentine ant , Linepithema humile , was the numerically predominant ant species and was associated with signifi cant reductions of other ant species captured. Stringer et al ( 2009 ) conducted extensive surveys across major New Zealand urban centres, and obtained 22 of the 38 ant species then known from New Zealand. L. humile occurred in 22 cities and traps with Argentine ants contained signifi cantly fewer (competing) ant species than traps without them, implying that L. humile signifi cantly affected other ant species encountered -this is a widely reported response to invasions by this species.…”
Section: Alien Insectsmentioning
confidence: 99%
“…Their study supported perceptions that the heat-island effect may have already facilitated such movements, with cities acting as corridors for continued range expansions of both native and alien species with those advantages. Increased urbanisation in New Zealand was believed to provide refuges during cooler periods for the warm temperate to subtropical region introduced ant species present, and to facilitate displacement of native ant species (Stringer et al 2009 ). In latitudinal comparisons throughout the country, the furthest north (warmest) urban sites had greater chances of yielding introduced ants.…”
Section: The Heat Island Effectmentioning
confidence: 99%